So witzig wie möglich, so ernst wie nötig: : Humor in den Medienkonferenzen des Schweizer Bundesrates im Jahr 2020 - Guhe, Sabrina (Linguistik Online, 2023)
This paper exposes the idea of humour as a strategy for coping with the COVID-19 pandemic in 2020. By focusing on the Swiss federal council’s media conferences, it aims at evaluating specific linguistic and thematic features which constitute humour. The analysis highlights the importance of everyday topics in dealing with the coronavirus and shows that the humorous potentiality in the press conferences’ oral communications is specified by laughing expressions and even more so that the humorous interactions occur at specific moments.